2004
DOI: 10.1136/bmj.38176.685208.f7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of congenital colour vision deficiency on education and unintentional injuries: findings from the 1958 British birth cohort

Abstract: Congenital colour vision defects (CVD) are common, inherited (most commonly X linked), non-progressive, and untreatable disorders.1 2 Screening children for these disorders is established practice in the United Kingdom, primarily so that those affected can be advised about occupational preclusions.2 Population based work on the broader impact of colour vision defects is, however, limited. Participants, methods, and resultsWe investigated the association between CVD and education and unintentional injury in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 4 publications
2
37
0
4
Order By: Relevance
“…Being taller and heavier than their peers was an independent risk factor for fractures in children from New Zealand,39 while post-primary school UK boys were more likely to sustain road traffic injuries if of short stature 40. The latter study also reported increased risk of traffic injuries with sensory deficit (unspecified), in contrast with papers reporting no increased risk of any injury associated with colour vision deficit41 or amblyopia 42. Studies exploring the impact of poor coordination or motor development found little evidence of independent increased risk in cohorts from both the UK40 and New Zealand 43…”
Section: Resultsmentioning
confidence: 78%
“…Being taller and heavier than their peers was an independent risk factor for fractures in children from New Zealand,39 while post-primary school UK boys were more likely to sustain road traffic injuries if of short stature 40. The latter study also reported increased risk of traffic injuries with sensory deficit (unspecified), in contrast with papers reporting no increased risk of any injury associated with colour vision deficit41 or amblyopia 42. Studies exploring the impact of poor coordination or motor development found little evidence of independent increased risk in cohorts from both the UK40 and New Zealand 43…”
Section: Resultsmentioning
confidence: 78%
“…In contrast, a 2004 cohort study on 499 CVD children found that CVD did not cause significantly lower scores in mathematics and reading at 7 years and 16 years of age respectively, even after adjusting for birth-weight, social class at birth, family size, and parental education [21]. Furthermore, the highest educational qualification was not significantly associated with colour vision status [21]. Another 2004 questionnaire survey showed no significant difference in the disciplines studied between NCV and CVD persons, but CVD interviewees tended towards technical studies (30%, as opposed to 18% of NCV subjects), and less of them undertook tertiary education in university (68.9%, as opposed to 79.9% of NCV subjects) [22].…”
Section: School Agementioning
confidence: 81%
“…A subsequent study in 1998 showed significantly lower general academic scores among 82 children with CVD as compared to 82 children with NCV, matched by age and class [20]. In contrast, a 2004 cohort study on 499 CVD children found that CVD did not cause significantly lower scores in mathematics and reading at 7 years and 16 years of age respectively, even after adjusting for birth-weight, social class at birth, family size, and parental education [21]. Furthermore, the highest educational qualification was not significantly associated with colour vision status [21].…”
Section: School Agementioning
confidence: 92%
See 2 more Smart Citations